Making Shops from Blogs: An Emerging Online Retailing Phenomenon in Southeast Asia. - Lim, Rodney; Diaz, Justo Amador; Dash, Debiprasad (Faculty of Computer Science and Information Technology, 2013)
Operating as mini online shops hosted on freely available social media such as blogs and social networking sites, blogshops have quietly emerged to become significant platforms for mass participation in e-commerce in Singapore and Malaysia. This paper introduces the blogshop and establishes it as the development of a unique socially-oriented approach to e-commerce. It reports findings from a pilot study that describes its unique attributes and the way they operate.